Design and Development of a Charge-Sensitive Preamplifier for Nuclear Pulse Processing (International Journal of Scientific Research and Management (IJSRM), 2013)
Authors attempt to describe a Charge-Sensitive Preamplifier for fast Pulse Processing. The charge sensitive preamplifier uses a capacitor in place of the feedback resistor. The input capacitance of this circuit is Cin = ACf, where A is the open-loop gain of the op-amp. If the op-amp gain is high enough that Ci << Cin, the external capacitance can be neglected. The charge Q is stored onto the feedback capacitor Cf, producing an output pulse of height V= -Q/Cf independent of the detector and stray capacitances. Since there is a high voltage on the detector electrode, the amplifier input is connected to the cathode of the GM detector through a ground full-up Resistor.